An investigation and evaluation of computer-aided design model complexity metrics. Issue 1 (2nd January 2018) - Johnson, Michael D.; Valverde, Lauralee M.; Thomison, William D.
ABSTRACT: Computer-aided design (CAD) tools are vital to the modern product commercialization process. CAD models and modeling activities are evaluated for various industrial, educational, and research purposes. However, there are no standard objective complexity metrics to use when evaluating these models or modeling procedures. Researchers and educators are often forced to use ad hoc quantities to normalize or account for CAD component variability. This work uses both quantitative and qualitative subjective assessments of CAD model complexity to evaluate objective geometric complexity metrics for CAD. These geometric complexity metrics are then compared to CAD model attributes related to CAD model complexity and modeling procedures. Modeling procedure includes the amount of time spent engaging in particular modeling activities. Curved and irregular surfaces are deemed difficult to model. Subjective quantitative assessments are found to be significantly correlated with objective geometric complexity metrics. Certain geometric complexity metrics are found to be related to computational processing time. Geometric metrics normalized by the number of features in a component are found to be significantly negatively correlated with modeling time. These results provide evidence of the relationship between the use of fewer features and modeling efficiency for components of a given complexity. GRAPHICAL ABSTRACT: